GAG Multivalent Systems to Interact with Langerin - Rojo, Javier; Nieto, Pedro M.; de Paz, José L. (Current Medicinal Chemistry, 2022)
Langerin is a C-type Lectin expressed at the surface of Langerhans cells, which play a pivotal role protecting organisms against pathogen infections. To address this aim, Langerin presents at least two recognition sites, one Ca2+-dependent and another one independent, which are capable to recognize a variety of carbohydrate ligands. In contrast to other lectins, Langerin recognizes sulfated glycosaminoglycans (GAGs), a family of complex and heterogeneous polysaccharides present in the cell membrane and the extracellular matrix, at the interphase generated in the trimeric form of Langerin but absent in the monomeric form. The complexity of these oligosaccharides has impeded the development of welldefined monodisperse structures to study these interaction processes. However, in the last few decades, an improvement of synthetic developments to achieve the preparation of carbohydrate multivalent systems mimicking the GAGs has been described. Despite all these contributions, very few examples are reported where the GAG multivalent structures are used to evaluate the interaction with Langerin. These molecules should pave the way to explore these GAG-Langerin interactions.
Keywords: GAG